2023
DOI: 10.1007/s10142-023-00975-8
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization leading to simple sequence repeat (SSR) markers development in Shorea robusta

Abstract: Tropical rainforests in Southeast Asia are enriched by multifarious biota dominated by Dipterocarpaceae. In this family, Shorea robusta is an ecologically sensitive and economically important timber species whose genomic diversity and phylogeny remain understudied due to lack of datasets on genetic resources. Smattering availability of molecular markers impedes population genetic studies indicating a necessity to develop genomic databases and species-specific markers in S. ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 94 publications
1
5
0
Order By: Relevance
“…Maximum species (50%) was under 'fair' status and the same result was also found by Manna and Mishra (2017) in Lalgarh forest range of West Bengal, India. In the present study Shorea robusta showed good regeneration status which is similar to the status of Shorea robusta found in tropical moist deciduous forest in Northern India (Mishra et al, 2023) and Ranchi Sal Forest in Eastern India (Kumar & Saikia, 2020), whereas the fair regeneration status of Sal was found in Lalgarh forest range of west Bengal, India (Manna & Mishra, 2017). In the current investigation, the adult stage was absent in all species, so the condition of "no regeneration" was not observed.…”
Section: Discussionsupporting
confidence: 82%
“…Maximum species (50%) was under 'fair' status and the same result was also found by Manna and Mishra (2017) in Lalgarh forest range of West Bengal, India. In the present study Shorea robusta showed good regeneration status which is similar to the status of Shorea robusta found in tropical moist deciduous forest in Northern India (Mishra et al, 2023) and Ranchi Sal Forest in Eastern India (Kumar & Saikia, 2020), whereas the fair regeneration status of Sal was found in Lalgarh forest range of west Bengal, India (Manna & Mishra, 2017). In the current investigation, the adult stage was absent in all species, so the condition of "no regeneration" was not observed.…”
Section: Discussionsupporting
confidence: 82%
“…NGS techniques have simplified the identification and characterization of microsatellites, establishing them as valuable markers in ecology and evolution for non-model species [64,65]. NGS techniques enabled the reliable discovery of microsatellite markers, a usual method for the description of de novo microsatellites applied in recent studies [66][67][68][69][70]. In this study, we successfully characterized new loci and mitochondrial genomes while performing optimization and cross-species validation of multiplex assays in four species of supralittoral Ochthebius.…”
Section: Discussionmentioning
confidence: 99%
“…Touchdown PCR was performed using a thermal cycler machine (Eppendorf Mastercycler Nexus). Primer SRGMS310 was used (forward sequence: 5′-ATAACCCATGTCCTGCCCAA-3′ and reverse sequence: 5′-GAATGGCCATGATTTGCCCC-3′) [ 6 ]. The amplification was performed in a 15 µl PCR reaction mixture, containing 30 ng of template DNA, 7.5 µl of 2× Taq mix (Composition: 2× Taq buffer (Cat.…”
Section: Methodsmentioning
confidence: 99%
“…Among Asian dipterocarps, predominantly in the Indian sub-continent, Shorea robusta (Vern: Sal) is an ecologically sensitive and commercially valuable woody species whose genetic diversity and phylogeny are currently uncertain due to a scarcity of data [ 6 ]. It is a prominent high-quality tree species for commercial timber production for revenue generation, as well as an outstanding supplier of construction material, tannin, gum, and oil, alongside being used as fodder and firewood [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation